The structural, optical and electrical properties of nanocrystalline ZnO: Al thin films - Benhaoua, Boubaker; Rahal, Achour; Benramache, Said (Academic Press, 2014)
The Al doped ZnO thin films were deposited by ultrasonic spray technique. The influence of Al doping on structural, optical and electrical properties of the ZnO thin films was studied. A set of Al doped ZnO (0–3.5 wt.%) were deposited at 350 °C. Nanocrystalline films with a hexagonal wurtzite structure with a strong (0 0 2) preferred orientation were observed after Al doping. The maximum value of grain size (33.28 nm) is attained with Al doped ZnO at 3 wt.%. Texture coefficient TC(h k l) of the four major peaks where evaluated. Optically, in visible region the transmissions spectra T(λ) show that the whole doped films exhibit lower values than the non doped one which has as transmittance more than 80%; whereas in the same region the optical transmissions of the doped films are affected by the doping ration. The band gap (Eg) increased after doping from 3.267 to 3.325 eV with increasing concentration of doping from 0 to 2.75 wt.%, respectively, according to the Burstein–Moss effect (blue shift of Eg) then beyond 3 wt.% in doping the band gap exhibit a slight decreasing due to the coexistence of Roth and Burstein–Moss effect. The electrical resistivity of the films decreased from 20 to 5.26 (Ω cm). The best results are achieved with 2.75 wt.% Al doped ZnO film.
Article
Keywords: ZnO:Al; Thin films; TCO; Ultrasonic spray technique